Donor-π-Conjugated Spacer-Acceptor Dye-Sensitized Solid-State Solar Cell Using CuI as the Hole Collector - D. N. Liyanage; K. D. M. S. P. K. Kumarasinghe; G. R. A. Kumara; A. C. A. Jayasundera; K. Tennakone; B. Onwona-Agyeman (International Journal of Photoenergy)
Dye-sensitized solid-state solar cells (DSSCs) replacing the liquid electrolyte with a p-type semiconductor have been extensively examined to solve the practical problems associated with wet-type solar cells. Here, we report the fabrication of a solid-state solar cell using copper iodide (CuI) as the hole conductor and alkyl-functionalized carbazole dye (MK-2) as the sensitizer. A DSSC sensitized with MK-2 showed a solar-to-electrical power conversion efficiency of 3.33% with a Voc of 496 mV and a Jsc of 16.14 mA cm-2 under AM 1.5 simulated sunlight. The long alkyl chains act as a barrier for charge recombination, and the strong accepting and donating abilities of the cyanoacrylic and carbazole groups, respectively, enhance the absorption of light at a longer wavelength, increasing the short-circuit current density. The efficiency recorded in this work is higher than similar DSSCs based on other hole collectors.